Effectiveness of extracorporeal shock wave therapy in patients with tennis elbow: A meta-analysis of randomized controlled trials. Issue 30 (24th July 2020) - Zheng, Chenxiao; Zeng, Dongjie; Chen, Jiayi; Liu, Sijing; Li, Jianyi; Ruan, Zhaohai; Liang, Wusheng
Abstract: Background: The aim of the present study was to investigate the effectiveness of Extracorporeal Shock Wave (ECSW) in the treatment of lateral epicondylitis (LE) of humerus. Hypothesis: ECSW therapy in people with LE effectively reduces the pain and gains functional rehabilitation. Materials/Methods: Databases of PubMed, EMBASE, Web of Science and the Cochrane Library from inception to April 2020 was searched to identify all relevant RCTs comparing ECSW therapy with any other conservative treatment, including injection and local anesthetic versus placebo or control in patients aged 18 with LE. The primary outcome is the mean overall pain score at 12 weeks after treatment. Another secondary outcome mainly included Thomsen test, 50% pain reduction, grip strength and adverse effect at 12 weeks after treatment. Results: Nine studies were included in the meta-analysis. Compared with the placebo group, ECSW cannot significantly reduce the pain score (mean deviation [MD] = -4.23, 95% confidence interval [CI]: -8.78 to 0.32, P  = .07), but make more people acquire 50% pain reduction (MD = 1.38, 95% CI: 1.09 to 1.75, P  = .008). There was no significant difference between ECSW and control in decreasing the pain score of Thomsen test (MD = -3.22, 95% CI: -14.06 to 7.62, P  = .56). ECSW was more effective in Grip strength as compared with control at 12 weeks-3 months (MD = 3.52, 95% CI: 2.43 to 4.60, P  < .00001) Conclusions: Results suggested that ECSW cannot effectively reduce the mean overall pain, but it showed more people acquire 50% pain reduction and might be a better option for the treatment of LE. Because of study limitations, additional high level of evidence, more rigorously designed large-samples and high-quality randomized controlled trials are needed to guide clinical practice. Abstract : Supplemental Digital Content is available in the text